2010
DOI: 10.1208/s12248-010-9220-2
|View full text |Cite
|
Sign up to set email alerts
|

Application of Quantitative Pharmacology in Development of Therapeutic Monoclonal Antibodies

Abstract: Abstract. The advancement of therapeutic monoclonal antibodies during various stages of the drug development process can be effectively streamlined when appropriate translational strategies are applied. Design of successful translational strategies for development of monoclonal antibodies should allow for understanding of the dose-and concentration-response relationships with respect to both beneficial and toxic effects from early phases of drug development. Evaluation of relevant biomarkers during early stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 98 publications
1
17
0
Order By: Relevance
“…1). Critical target-related properties are (a) expression profile, and density (receptor copy number), (b) target internalization and turnover rate, and (c) functional relevance to human disease (18)(19)(20). An ideal target should demonstrate a specific expression profile at the relevant site of action (typically tumor cells) with little to no expression in other healthy tissues (18,19).…”
Section: Considerations For Target Selection and Modality Designmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Critical target-related properties are (a) expression profile, and density (receptor copy number), (b) target internalization and turnover rate, and (c) functional relevance to human disease (18)(19)(20). An ideal target should demonstrate a specific expression profile at the relevant site of action (typically tumor cells) with little to no expression in other healthy tissues (18,19).…”
Section: Considerations For Target Selection and Modality Designmentioning
confidence: 99%
“…The two key target-related parameters affecting drug concentration at the intracellular site are expression density of the target receptor and its internalization or turnover rate which define the target capacity (20). Understanding the t a r g e t c a p a c i t y -t h e i n t e r p l a y b e t w e e n t h e s e parameters-provides a rational approach for target selection.…”
Section: Impact Of Target Density and Internalization Rate On Payloadmentioning
confidence: 99%
“…boswell.charles@gene.com) ABBREVIATIONS: ADME, Adsorption distribution, metabolism, and excretion; Fc, Crystallizable fragment; DTPA, Diethylenetriaminepentaacetic acid; DOTA, 1,4,7,20- Although nonradioactive, bioanalytical methods are still regarded as the industry standard (13), the use of radionuclides in the quantitative pharmacology of antibodies boasts extremely high sensitivity and well-established methods for incorporation and detection (14). But perhaps the most important advantage lies in the facile detection of radionuclides in tissues for biodistribution studies (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…The increasing interest in biologicals in general, and mAbs in particular, is partly due to their high success rate during preclinical and clinical development [1]. It has been suggested that an important element that has contributed to this success is the fact that, compared to small molecules, the pharmacokinetic-pharmacodynamic (PKPD) properties of mAbs are more amenable to quantitative, mechanistic modelling and simulation (M&S)-based translation approaches across preclinical and clinical research [2,3,4,5]. A specific example of this is the implementation of the principles of target-mediated drug disposition (TMDD) into quantitative pharmacological models to describe and predict PKPD behaviour of mAbs.…”
Section: Introductionmentioning
confidence: 99%
“…PK and PD become interdependent. Mager and Jusko [7] were the first to propose a general PK model for drugs exhibiting TMDD, which has provided the basis for extensive further studies and development (see for example [8,9,10,11,5]). Experimental confirmation of TMDD model predictions was provided in a recent elegant study by Abraham et al [12], who showed marked differences in interferon (INF)-β PK in wild-type and type-1 INF α/β receptor knockout mice.…”
Section: Introductionmentioning
confidence: 99%